2004
DOI: 10.1002/ajmg.b.20164
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐related genes in patients with panic disorder

Abstract: Enhanced respiratory variability and decreased heart rate variability have repeatedly been observed in patients with panic disorder. Prompted by the notion that angiotensin may be involved in the control of respiration, heart rate variability, and anxiety-like behavior, we investigated the putative association between polymorphisms in three angiotensin-related genes and panic disorder-angiotensinogen (AGT), angiotensin converting enzyme (ACE), and angiotensin II (ANG II) receptor type 1 (ATr1) in 72 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 32 publications
5
42
1
Order By: Relevance
“…One pathway related to both respiration and cardiovascular control is the angiotensin system (Atlas 2007;Jennings 1994;Olsson et al 2004b), which has also been suggested to be involved in the pathophysiology underlying PD (Shekhar et al 2006). Supporting the notion that genes of importance for autonomic regulation may be involved in panic disorder , we have previously shown the I allele in the functional angiotensin converting enzyme insertion/deletion polymorphism to be significantly more frequent in male PD patients as compared to controls (Olsson et al 2004c); a finding that has later been replicated by Bandelow and co-workers (Bandelow et al 2007).…”
Section: Are Genes Influencing Arousal And/or Respiration Involved Insupporting
confidence: 56%
See 1 more Smart Citation
“…One pathway related to both respiration and cardiovascular control is the angiotensin system (Atlas 2007;Jennings 1994;Olsson et al 2004b), which has also been suggested to be involved in the pathophysiology underlying PD (Shekhar et al 2006). Supporting the notion that genes of importance for autonomic regulation may be involved in panic disorder , we have previously shown the I allele in the functional angiotensin converting enzyme insertion/deletion polymorphism to be significantly more frequent in male PD patients as compared to controls (Olsson et al 2004c); a finding that has later been replicated by Bandelow and co-workers (Bandelow et al 2007).…”
Section: Are Genes Influencing Arousal And/or Respiration Involved Insupporting
confidence: 56%
“…Val158Met polymorphism , the angiotensin converting enzyme insertion/deletion polymorphism (Bandelow et al 2007;Erhardt et al 2008;Olsson et al 2004c), and the adenosine 2A receptor polymorphism (Deckert et al 1998;Hamilton et al 2004).…”
Section: Geneticsmentioning
confidence: 99%
“…While it was reported that bipolar disorder was not associated with I/D polymorphism 27 , another study suggested that it was associated with I/D genotype in the Asian race 28 . ACE gene polymorphism was reported not to be related to panic disorder 29,30 , although the frequency of I allele is higher in men than women 31 . Another study stated that there was an association between ACE gene polymorphism and MDD only in female patients 32 , as consistent to our results.…”
Section: Discussionmentioning
confidence: 95%
“…In a historical population-based cohort study, we reported a nearly sixfold increased risk of autism in the offspring of Israeli fathers aged 40 years and older compared to those under 30 years, 1 a finding observed in several other samples. 2,3 While we suggested that accumulating de novo mutations in the spermatogonia of older fathers might account for this finding, 1 an alternative explanation is that deferred paternity is a function of genetic traits present in the fathers of autistic children. Personality traits such as aloofness, rigidity, anxiousness and hypersensitivity, collectively called the broader autism phenotype (BAP), are overexpressed in unaffected relatives of autism probands.…”
mentioning
confidence: 87%
“…A Japanese study failed to detect an effect, whereas two European studies reported a significant association of the less active I allele with panic disorder mainly in the male subgroup of panic patients. [3][4][5] To further elucidate the role of the ACE in the genetic vulnerability for panic attacks, we first genotyped the 24 single nucleotide polymorphisms (SNPs) covering the ACE gene region (710 kb) reported in Baghai et al (2006), in 175 patients with syndromal panic attacks (including panic disorder with and without agoraphobia 87.7%, social and special phobia 13.3%), who were recruited from our Anxiety Disorders Outpatient Clinic, versus 445 healthy controls matched for ethnicity, age and sex (sample 1, Max Planck Institute for Psychiatry (MPI)). Patients and controls underwent a thorough clinical and laboratory examination.…”
mentioning
confidence: 99%